Ответ:
Объяснение:a)(2a-b)(2a+b)=4a²-b²;
b)(x+5)²=x²+10x+25;
c)(x-1)(x²+x+1)=x³-1;
d) (3a²+2b)³=27a⁶+54a⁴b+36a²b²+8b³.
(действуют формулы сокращенного умножения,выпиши их для себя и выучи)
a) (2a-b)(2a+b)=4a²+2ab-2ab-b² = 4a²-b²
б) (x+5)²=x²+10x+25
в) (х-1)(х²+х+1)=х³+х²+х-х²-х-1=х³-1
г) (3а²+2b)³=(3a²)³+3*(3a²)³*2b+3*3a²*(2b)²+(2b)³=27a⁶+54a⁴b+36a²b²+8b³
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
Объяснение:a)(2a-b)(2a+b)=4a²-b²;
b)(x+5)²=x²+10x+25;
c)(x-1)(x²+x+1)=x³-1;
d) (3a²+2b)³=27a⁶+54a⁴b+36a²b²+8b³.
(действуют формулы сокращенного умножения,выпиши их для себя и выучи)
Ответ:
a) (2a-b)(2a+b)=4a²+2ab-2ab-b² = 4a²-b²
б) (x+5)²=x²+10x+25
в) (х-1)(х²+х+1)=х³+х²+х-х²-х-1=х³-1
г) (3а²+2b)³=(3a²)³+3*(3a²)³*2b+3*3a²*(2b)²+(2b)³=27a⁶+54a⁴b+36a²b²+8b³